PRE-SERVICE ENGLISH AS A FOREIGN LANGUAGE (EFL) TEACHERS’ MOTIVES TO BECOME TEACHERS: A COMPARATIVE STUDY - Puput Arfiandhani; Ika Wahyuni Lestari (ETERNAL (English, Teaching, Learning and Research Journal), 2019)
This study aimed to compare the male and female pre-service teachers’ motives in becoming EFL teachers and to find out whether there was any difference between male and female pre-service teachers’ motives to become teachers. The quantitative research with survey design was applied to collect the data from three private teacher-training institutions of Yogyakarta, Indonesia. SPSS 24 was used to analyze the data. The findings indicated that the Sig. (2-tailed) value was 0.612 higher than 0.05 (alpha) and the descriptive statistical analysis proved that the mean score between female (N=96) and male (N=36) pre-service teachers’ motivation was relatively same. The mean score for female was 2.90 with the standard deviation of 0.38 and for male was 2.94 with the standard deviation of 0.26. Therefore, there was no difference between male and female pre-service teachers’ motivation in three teacher-training institutions of Yogyakarta.